Development and Validation of a Method for Detecting and Quantifying Mitragynine in Kratom Samples Using HPLC-PDA - Isnaeni, Neni; Saefumillah, Asep; Cahyana , Antonius Herry (Eruditio : Indonesia Journal of Food and Drug Safety, 2024)
Kratom (Mitragyna speciosa Korth) has been identified as a New Psychoactive Substance (NPS) by the United Nations Office on Drugs and Crime (UNODC) and included in the list of prohibited ingredients in food supplements and traditional medicine by Indonesian FDA. Therefore, a rapid, easy, and reliable analytical method is necessary to detect and quantify this plant and its products. This study developed a method for the detection and quantification of kratom products based on a unique compound, mitragynine, as a biomarker. A previous survey of determining mitragynine in Kratom using GC-MS, LC-MS/MS, UPLC, and HPLC-PDA. Previously, the HPLC-PDA method used a C8 column. Yet, for efficiency, it is also necessary to develop a test method using a C18 column. Analysis was performed using an HPLC - PDA system with Waters Atlantis T3-C18 (250 x 4.6 mm, 5 µm) column. The mobile phase comprises acetonitrile and formic acid 0.05%, pH 5.0 (75:25 v/v), delivered at a 1.0 mL/min flow rate. Detection was carried out at a wavelength of 225 nm. The analytical method was validated with test parameters of selectivity, system suitability, accuracy, precision, linearity, detection limit, and quantification limit. The validation study demonstrated an excellent linear concentration range of 1.96 - 6.01 µg/mL with a correlation coefficient of 0.9996; the detection limit is 0.14 µg/mL, while the limit of quantification is 0.45 µg/mL—accuracy method of 98.88 - 101.44% and a bias of 0.27%. The percent relative standard deviation for six independent assay determinations was 0.67%, and the intermediate precision was 1.56% on two days. The mitragynine amounts in these materials ranged from 6.01 to 6.31 mg/g of dried leaf material. Based on the research results, it can be concluded that the method developed provides quick, simple, reliable, accurate, and valid, and has an advantage over existing methods in terms of simplicity of sample preparation, short analysis time, and cost-effectiveness compared to GCMS and LCMS/MS and can be applied for future analysis in Kratom samples.